Time efficiency as a mediator between institutional support and higher education student engagement during e-learning - Tarik Abdulkrem Alwerthan (PLoS ONE, 2025)
This study examined the relationship between institutional support and student engagement in e-learning, with time efficiency as a potential mediator among Saudi university students. This study employed a cross-sectional, questionnaire-based research design. A sample of 752 Saudi university students from different provinces in the Kingdom of Saudi Arabia completed an online questionnaire. The results of the measurement model showed good reliability and validity for all constructs. The results of the structural model and hypothesis testing showed that this study partially supported the hypotheses. Notably, there was a significant positive relationship between student support during e-learning and student engagement. In addition, student support was found to be a predictor of student’s time efficiency (short-term planning, long-term planning, time attitude). Furthermore, the results revealed that long-term planning and time attitude, both components of time efficiency, act as mediators between support provided to students by a higher education (HE) institution during e-learning and their level of engagement. The findings shed light on the underlying mechanisms that explain students’ e-learning engagement.